Faktor penentu setting fisik aktivitas Taman Lapangan Jawa di Kota Depok - Hasibuan, Moh. Sanjiva Refi; Syahadat, Ray March (Jurnal Arsitektur Lansekap, 2020)
The existence of parks is one of the solutions in solving urban environmental problems. Not only has an ecological function, but the park also has a social function. The Jawa Park field is one of the neighbourhood parks in Depok that is actively used by local residents. One of the problems that is often encountered in neighbourhood parks is a mismatch of park design with the users' needs which raises issues regarding the sustainability of the park. For this reason, an evaluation is needed to determine how well the Lapangan Jawa Park can accommodate the needs in accordance with the behavior of its users. The methods that are used in this article were observation to identify park characters and observation of user behavior using the behavior setting approach. The data is analyzed descriptively using image processing software. The results are obtained, there are several important things that determine the physical settings of Lapangan Java Park activities in order to achieve sustainability. As for things that need to be considered include corrections to the entrance space in the north area of ??the park, parking area needs, recalculate the number and placement for the bench, and the reduction in the size of sports spaces that are not so used by the park users.